2021
DOI: 10.3389/fimmu.2021.720183
|View full text |Cite
|
Sign up to set email alerts
|

FHR-5 Serum Levels and CFHR5 Genetic Variations in Patients With Immune Complex-Mediated Membranoproliferative Glomerulonephritis and C3-Glomerulopathy

Abstract: BackgroundFactor H-related protein 5 (FHR-5) is a member of the complement Factor H protein family. Due to the homology to Factor H, the main complement regulator of the alternative pathway, it may also be implicated in the pathomechanism of kidney diseases where Factor H and alternative pathway dysregulation play a role. Here, we report the first observational study on CFHR5 variations along with serum FHR-5 levels in immune complex-mediated membranoproliferative glomerulonephritis (IC-MPGN) and C3 glomerulop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…include C3, CFB, CFH, CFI, DGKE, and CFHR5. In addition, the CFHR genomic region should be screened for complex rearrangements typically by multiplex-ligation-dependent probe amplification (MLPA), a multiplex PCR-based method that can detect the copy number of each CFHR gene.When exon-specific probes are used, CFHR genomic rearrangements such as the CFHR5 fusion gene endemic to Cyprus can be easily identified(Gale et al, 2010;Garam et al, 2021;Schouten et al, 2002).…”
mentioning
confidence: 99%
“…include C3, CFB, CFH, CFI, DGKE, and CFHR5. In addition, the CFHR genomic region should be screened for complex rearrangements typically by multiplex-ligation-dependent probe amplification (MLPA), a multiplex PCR-based method that can detect the copy number of each CFHR gene.When exon-specific probes are used, CFHR genomic rearrangements such as the CFHR5 fusion gene endemic to Cyprus can be easily identified(Gale et al, 2010;Garam et al, 2021;Schouten et al, 2002).…”
mentioning
confidence: 99%
“…110,111 One of these studies also showed that the reduced FHR-5 levels were independent of the presence of CFHR5 null alleles, and that the levels correlated positively with the levels of C3, C4, FH and the activity of the AP and the CP, suggesting that FHR-5 is consumed upon complement activation. 110 A study by Pouw et al…”
Section: Quantitative Variations Of the Fh Protein Familymentioning
confidence: 93%
“…Similarly, FHR‐5 plasma levels were also significantly elevated in IgAN, but whether this is due to genetic or environmental factors is unknown 57 . In contrast, reduced plasma FHR‐5 levels compared with controls have been observed in different cohorts of C3G and in immune complex‐mediated membranoproliferative glomerulonephritis 110,111 . One of these studies also showed that the reduced FHR‐5 levels were independent of the presence of CFHR5 null alleles, and that the levels correlated positively with the levels of C3, C4, FH and the activity of the AP and the CP, suggesting that FHR‐5 is consumed upon complement activation 110 .…”
Section: The Factor H Protein Family In Diseasementioning
confidence: 98%
See 1 more Smart Citation
“…While FHL-1 retains the same function as its larger FH counterpart, the FHR proteins are FH/FHL-1 antagonists and drive complement activation instead of inhibition ( 21 ). Altered levels of these proteins play a key role in several complement-related diseases, including renal diseases such as atypical haemolytic uremic syndrome (aHUS), C3 glomerulopathy (C3G) ( 22 , 23 ) and Age-Related Macular Degeneration (AMD) ( 24 ). FHRs 2 and 5 have also been identified as potentially differentially expressed in association with severe COVID-19 in global proteomics studies ( 12 , 25 ).…”
Section: Introductionmentioning
confidence: 99%